STUDY AND CLASSIFICATION OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The importance of phraseological units is high in any language since they make speech meaningful, colorful, and emotional. In this article, the study of phraseological units and their classification are analyzed in detail. In addition, as phraseology is a broad theme that involves different objects such as phraseological units, proverbs, and sayings, it requires deep learning to differentiate them from each other. For this reason, the author focused on some aspects of phraseology, such as the origin of phraseology as a separate field of linguistics as well as the development of it in the Uzbek language, along with examples that serve as proof of the conclusion